THE REPRESENTATIONS OF CHARACTER EDUCATION VALUES IN ENGLISH TEXTBOOK WHEN ENGLISH RINGS A BELL - Brenda Khanadi; Ni Komang Arie Suwastini; Kadek Eva Krishna Adnyani; Ni Luh Putu Sri Adnyani; I Gusti Agung Sri Rwa Jayantini (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2022)
ABSTRACTThe present study analyzed the representations of the Five Core Values of character education recommended by the Indonesian Ministry of National Education in 2017 into a national English Textbook for 7th Grade, entitled When English Rings a Bell. The present study was qualitative research, which conducted the data classification, data display, and conclusion drawing concurrently and repeatedly, while the whole process is always compared with the data collection. The study revealed that the book investigated represents all five core values: religiosity, nationalism, independence, cooperation, and integrity. Religiosity and nationalism were the two values most cultivated in the textbook, while integrity is represented more infrequently, and cooperation value is sparsely presented. These findings imply that the imbalanced representation of the five core values in the textbook investigated could negatively affect the students’ character building. Thus, the present study recommends teachers use this textbook to design activities that call for cooperation and integrity values, so the students’ character building at school can be more balanced. ABSTRAKPenelitian ini mencermati representasi Lima Nilai Utama Pendidikan Karakter yang direkomendasikan Kementrian Pendidikan dan Kebudayaan pada 2017 ke dalam buku teks Bahasa Inggris untuk Kelas VII berjudul When English Rings a Bell. Kajian ini dirancang sebagai penelitian kualitatif deskriptif, dimana kategorisasi data, pemaparan data, dan penarikan kesimpulan dilakukan bersamaan dan berulang, serta selalu dibandingkan dengan proses dan hasil pengumpulan data. Ditemukan bahwa buku teks yang dikaji mengandung representasi kelima nilai utama pendidikan karakter yang direkomendasikan kementrian: religius, nasionalis, mandiri, gotong royong, dan integritas. Nilai religius dan nasionalis adalah dua nilai yang paling sering dihadirkan, sementara intgritas dihadirkan cukup sering dan nilai gotong royong merupakan nilai yang paling jarang. Temuan ini menunjukkan bahwa ada ketidakseimbangan dalam representasi kelima nilai utama pendidikan karakter dalam buku teks yang dikaji, yang dapat berimplikasi negative pada pengembangan karakter anak. Untuk itu, penelitian ini menyarankan agar guru mengimbangkan ketimpangan pada buku teks ini dengan merancang kegiatan-kegiatan yang mengembangkan nilai gotong royong dan integritas sehingga usaha penguatan karakter siswa dapat berlangsung dengan lebih baik dalam pembelajaran di sekolah.